MAKNA ASET YANG MELEKAT PADA ANAK DALAM PERSPEKTIF AKUNTAN PENDIDIK - Mikail Rizki Heryawan; Krisno Septyan (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to dig deeply into the meaning of children as assets in a family. The method used in this study is a qualitative method with a phenomenological approach. The informant in this study were three informants who worked as lecturers in financial accounting because the researcher intends to bring the meaning of assets into the family environment. Based on the research carried out, it was found that children have an important meaning in the family and also the meaning of assets attached to children, namely as the fruit of happiness which means children as carriers of happiness in the family, gifts for the gift of God Almighty which means that children are a mandate from God Almighty so that they must be taken care of properly, and children are intangible assets that can provide benefits to the wider community. The implication of this research is to encourage parents to educate their children well so that they can benefit the wider community.